Radio Broadcasters Credibility as 'Spokespersons' Raising The Adlibs - M Rizky Kertanegara (Atma Jaya Indonesia Catholic University, Jakarta, 2016)
In the midst of the rapid development of communication technology, it would make the pattern of the clients of a product or service in the marketing communications activities shift from traditional media to new media. However, advertising through traditional media is still required and still effective in marketing their products or services. One of the surviving media is radio advertising through adlibs. Adlibs is advertising material that was delivered directly by a broadcaster in a program. In the perspective approach to advertising messages, radio broadcaster's role can be categorized as a spokesperson or the person who spoke on behalf of the company to present their products or services in the form of credibility. Eisend (2002) conceptualized the spokesperson's credibility on the dimensions of honesty, objectivity, charisma, and competence. Thus, this study wanted to explain how the concept of the credibility of the broadcaster, as a product spokesperson, in conveying adlibs within the scope of marketing communications as well as the effectiveness of advertising messages.